SISTEM HUKUM KEWARISAN ISLAM DI INDONESIA - Wulan Permata Sari; Usep Saepullah; Seilla Nur Amalia; Murni Rossyani (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2024)
In Indonesia, there is currently no universal law of inheritance that applies to all citizens. This is because the inheritance system in Indonesia is divided into three, namely Islamic inheritance law, inheritance law based on the Book of Civil Law, and inheritance law based on local customs. In the context of Islamic inheritance law, the Religious Court plays a central role as a separate institution with full authority in resolving inheritance disputes for Muslim communities. This aligns with the teachings of the Prophet, emphasizing the importance of applying Islamic inheritance law to prevent disputes over inheritance. This study aims to analyze Islamic inheritance law from its concepts, legal sources, principles, order of heirs, obstacles in inheritance, and procedures for dividing inheritance according to Islamic law. The research method used is a library method involving relevant books and journals. The research results show that Islamic inheritance law covers who is entitled to inheritance, the size and reduction of inheritance portions, and the implementation of inheritance distribution. This is based on legal norms sourced from the Quran, Hadith, Ijma, and Ijtihad of Ulama, which must be followed by all society.